2021
DOI: 10.1002/jper.21-0076
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic evaluation of the titanium‐prepared platelet‐rich fibrin effect in free gingival graft procedures

Abstract: Background Complications after free gingival graft (FGG) operations are generally related to the donor site. The titanium‐prepared, platelet‐rich fibrin (T‐PRF) placement in the donor site accelerate the wound healing and prevent postoperative complications such as pain and hemorrhage. We aim to evaluate the effect of T‐PRF regarding vascularization and tissue thickness and to report the advantages of the ultrasonography (US) in FGG. Methods Ten individuals were divided into two groups as T‐PRF and control. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Only one case series (with 3 patients per group) showed superior results for collagen hemostatic sponge in comparison to L‐PRF (Belkhede et al., 2019) and one RCT showed no differences between both groups (Alvarez‐Medina et al., 2023). Two studies reported better healing with palatal donor sites treated with titanium‐prepared platelet‐rich fibrin (T‐PRF) in comparison to collagen hemostatic sponge (Koca‐Ünsal et al., 2022) and acrylic stent (Gülbahar Ustaoglu et al., 2016). In addition, two studies also showed superior healing in palatal donor sites covered with A‐PRF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one case series (with 3 patients per group) showed superior results for collagen hemostatic sponge in comparison to L‐PRF (Belkhede et al., 2019) and one RCT showed no differences between both groups (Alvarez‐Medina et al., 2023). Two studies reported better healing with palatal donor sites treated with titanium‐prepared platelet‐rich fibrin (T‐PRF) in comparison to collagen hemostatic sponge (Koca‐Ünsal et al., 2022) and acrylic stent (Gülbahar Ustaoglu et al., 2016). In addition, two studies also showed superior healing in palatal donor sites covered with A‐PRF.…”
Section: Resultsmentioning
confidence: 99%
“…(1996) also reported that the use of microcollagen felt associated with periodontal dressing promoted faster healing in comparison to periodontal dressing alone, but not in comparison to fragments of connective tissue with epithelium removed from the graft associated with periodontal dressing. In comparison to L‐PRF, better wound healing was obtained for L‐PRF in comparison to collagen hemostatic sponge in four studies (Femminella et al., 2016; Hassan et al., 2020; Koca‐Ünsal et al., 2022; Sousa et al., 2020), however, collagen hemostatic sponge promoted superior repair in comparison to L‐PRF in one case series (Belkhede et al., 2019). In addition, collagen cones associated with gel based on recombinant human angiogenin promoted better repair in comparison to collagen cones alone (Goryachkin et al., 2019).…”
Section: Resultsmentioning
confidence: 99%